Eugenia neomattogrossensis Mazine, a replacement name for Eugenia mattogrossensis Mazine (Myrtaceae) - Mazine, Fiorella Fernanda (Phytotaxa, 2012)
Eugenia Linnaeus (1753: 470) is the largest genus in Myrtaceae, with the highest number of species of trees in the rainforests and semi-deciduous of the Brazilian Atlantic Forest region (Oliveira-Filho & Fontes 2000). Eugenia is currently estimated to contain ca. 1000 species (WCSP 2012), distributed from South of Mexico, Cuba, the Antilles to Uruguay and Argentina, with a small number of species (ca. 60) in Africa (Van der Merwe et al. 2005). Some species, with edible fruits are cultivated in tropical and subtropical regions (e.g., Eugenia uniflora L.(1753: 470) and Eugenia brasiliensis Lamarck (1789: 203)).